2023
DOI: 10.1101/2023.10.28.564455
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pushing the boundaries of MEG based on optically pumped magnetometers towards early human life

Pierre Corvilain,
Vincent Wens,
Mathieu Bourguignon
et al.

Abstract: Characterizing the early development of the human brain is critical from both fundamental and clinical perspectives. However, existing neuroimaging techniques are either not well suited to infants or have limited spatial or temporal resolution. The recent advent of optically pumped magnetometers (OPMs) has revolutionized magnetoencephalography (MEG) by enabling wearable and thus naturalistic recordings while maintaining excellent sensitivity and spatiotemporal resolution. Nevertheless, its adaptation to study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 67 publications
0
1
0
Order By: Relevance
“…Further, because sensors move with the head, movement is possible during a scan. OPM-MEG is, ostensibly, ideal for children; for example, Hill et al showed the viability of OPM-MEG in a 2 year old 32 ; Feys et al showed advantages for epileptic spike detection in children 33 , and Corvilain et al demonstrated utility even in the first weeks of life 34 . However, no studies have yet used OPM-MEG in large groups to measure neurodevelopment.…”
Section: Introductionmentioning
confidence: 99%
“…Further, because sensors move with the head, movement is possible during a scan. OPM-MEG is, ostensibly, ideal for children; for example, Hill et al showed the viability of OPM-MEG in a 2 year old 32 ; Feys et al showed advantages for epileptic spike detection in children 33 , and Corvilain et al demonstrated utility even in the first weeks of life 34 . However, no studies have yet used OPM-MEG in large groups to measure neurodevelopment.…”
Section: Introductionmentioning
confidence: 99%
“…Further, because sensors move with the head, movement is possible during a scan. OPM-MEG is, ostensibly, ideal for children; e.g., Hill et al showed the viability of OPM-MEG in a 2 year old ( Hill et al, 2019 ); Feys et al showed advantages for epileptic spike detection in children ( Feys et al, 2022 ), and Corvilain et al demonstrated utility even in the first weeks of life ( Corvilain et al, 2023 ). However, no studies have yet used OPM-MEG in large groups to measure neurodevelopment.…”
Section: Introductionmentioning
confidence: 99%